2020
DOI: 10.3390/molecules25225430
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Anti-Inflammatory Activity of Terpenes in Experimental Models (2010–2020): A Review

Abstract: Inflammatory bowel diseases (IBDs) refer to a group of disorders characterized by inflammation in the mucosa of the gastrointestinal tract, which mainly comprises Crohn’s disease (CD) and ulcerative colitis (UC). IBDs are characterized by inflammation of the intestinal mucosa, are highly debilitating, and are without a definitive cure. Their pathogenesis has not yet been fully elucidated; however, it is assumed that genetic, immunological, and environmental factors are involved. People affected by IBDs have re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 109 publications
(157 reference statements)
1
22
0
Order By: Relevance
“…Additionally, it has been shown to inhibit the nuclear factor kappa-enhancer of activated B cells (NF-kB), which are essential for viral protein production, and inhibit the activation of mitogen-activated protein kinases. Prior studies have demonstrated the anti-inflammatory effects of phytoncide in the body [74]. This study also revealed the anti-inflammatory effects of forest healing in that both IL-8 and TNF-α, which are associated with inflammation in vivo, significantly decreased after the forest healing program.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Additionally, it has been shown to inhibit the nuclear factor kappa-enhancer of activated B cells (NF-kB), which are essential for viral protein production, and inhibit the activation of mitogen-activated protein kinases. Prior studies have demonstrated the anti-inflammatory effects of phytoncide in the body [74]. This study also revealed the anti-inflammatory effects of forest healing in that both IL-8 and TNF-α, which are associated with inflammation in vivo, significantly decreased after the forest healing program.…”
Section: Discussionsupporting
confidence: 59%
“…Among the various factors involved in forest healing, phytoncide is known to have excellent anti-bacterial and anti-inflammatory effects, as it activates Toll-like receptors in the body, reducing inflammatory cytokines, such as IL-6 and TNF-α, as well as oxidative stress. [74]. Additionally, it has been shown to inhibit the nuclear factor kappa-enhancer of activated B cells (NF-kB), which are essential for viral protein production, and inhibit the activation of mitogen-activated protein kinases.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, as shown in Figure 3 , the available data suggest that triterpenes may modulate an imbalanced microbiome–gut–brain communication during impaired brain functions and promote mental health [ 207 , 209 , 210 , 211 , 212 , 213 ]. G. pentaphyllum , C. asiatica , and P. ginseng exerted prebiotic-like effects and led to a recovered intestinal flora diversity or mitigated gut dysbiosis compared with control groups in rodent models [ 82 , 115 , 116 , 120 , 142 , 144 , 149 ].…”
Section: Resultsmentioning
confidence: 95%
“…According to many preclinical studies, certain types of triterpenes possess anti-inflammatory, antioxidant, and antiapoptotic properties and thus may contribute to neuronal protection [ 206 , 213 ]. Moreover, triterpene glycosides can be metabolized by gut microbiota into better absorbable active metabolites that become systemically available [ 206 , 207 , 208 ].…”
Section: Resultsmentioning
confidence: 99%
“…Together with their well-studied bactericidal potential, these phenolic compounds are described to potentially improve the integrity of the mucosal tissues due to their observed antioxidant, anti-inflammatory and consequent immunomodulatory properties in the gastrointestinal mucosa of several animal models (112). The reported strong antioxidant activity of carvacrol and thymol rely on their ability to scavenge free radicals, inhibiting reactive oxygen species (ROS) and other oxygen radicals generated in cells and tissues (113).…”
Section: Effect Of Dietary Terpene Phenolic Compounds Upon Fish Mucosal Immunitymentioning
confidence: 99%